THE USE OF KHAFIF METERS IN UZBEK POETRY OF THE SECOND HALF OF THE 20TH CENTURY - Rakhmonova Shakhnoza Mukhitdinovna (Journals Park Publishing, 2024)
In this article, the meter of khafif sea used in Uzbek poetry of the second half of the 20th century is analyzed. In the ghazals of Habibi, Sabir Abdulla, and Charkhi, the continuation of classical traditions, as well as the features of meter and measurement possibilities of ghazals were studied. In the poetry of the period, the statistics of the meters of khafif sea were studied for the first time.
Keywords: Aruz, ghazal, masnavi, Vasli ho, khafif.